Study of the Architectural Forms Composition of the Ottoman Minarets Mosques in Constantine City-Algeria - Sekhri , Adel; Assassi , Abdelhalim; Mebarki , Ammar (Dirasat: Human and Social Sciences, 2023)
Objectives: The minarets are one of the most important elements of Islamic architecture that deserve study and attention, as they are a wonderful record of all the phases that Islamic art went through around the world. Therefore, they were chosen as the subject of this research by studying the composition of the architectural forms of the Ottoman minarets in the mosques of the city of Constantine-Algeria. This paper aims to answer the questions related to the formation and development of Ottoman minarets, and to search for the reasons behind the formation of their architectural forms in the mosques of Constantine city. Methods: The "Typomorphological approach" was chosen as a tool of the analytical method for studying the Ottoman minarets in the city. Results: The results showed that the reasons contributing to the formation of the Ottoman minarets in the city’s mosques were as follows: The functional exploitation of the minarets, the transformation of the minaret, into an Islamic symbol, in addition to doctrinal, technical, and military factors. Conclusions: Finally, it should be noted that the most important recommendation of the research is valuing this architectural heritage which represents the local identity of the city of Constantine, and opening a field of research aimed to study the architectural forms of Ottoman minarets in the mosques of the old city.